Informing patient contacts about iatrogenic Creutzfeldt–Jakob disease. Issue 2 (June 2020) - Brodbelt, A.R.; Vinten, J.; Larkin, S.
Summary: The unanticipated diagnosis of sporadic Creutzfeldt–Jakob disease (sCJD) in a patient after previous neurosurgery can lead to difficult decisions regarding informing contacts. A patient developed sCJD 3 years after neurosurgery. There were 29 potential contacts and 26 were contacted. Twelve completed a questionnaire. The majority of patients wished to know about the contact and to be seen face-to-face, and their main concern was developing the disease despite verbal and written reassurance that this was unlikely. Informing patients of sCJD contact is difficult and can lead to significant patient anxiety. Face-to-face meetings, a helpline and follow-up can help.